Kontaminasi Bakteri Escherichia coli Pada Permukaan Capsicum frutescens L. (Cabai Rawit) di Pasar Tradisional Wilayah Kota Semarang - Permana, Tantri Nur; Hestiningsih, Retno; Yuliawati, Sri (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Cayenne pepper is one of popular vegetables in our daily diet. But in recent years, the number of foodborne outbreaks from contaminated produce have sharply increased. The purpose of this research is to identify the presence of E. coli at surface cayenne pepper in traditional market of Semarang. This study uses survey method with cross-sectional approach. The sample in this research is the Cayenne Pepper sold in the traditional market of Semarang, total samples are 40 samples from 8 traditional markets. Data analysis using chi square. 87,5% of the entire sample of cayenne pepper E. coli positive diagnosed. On sample that planted in the Mc Conkey, based on visual observations, there are other bacterial colonies such as Salmonella spp, colony Enterobacter and Klebsiella spp. Based on the results of statistical tests, shows that time storage affected the number of colonies (p = 0,026) . The results showed that cayenne pepper contaminated with E. coli, so that more attention is needed to the hygiene of non-processed or fresh produce to be consumed.